Health of the War Worker (London : Labour Research Department)
1942-04 1942 1940s 44 pages a poor appetite, and constipation. T.N.T. gastritis needs to be taken seriously. The most serious result from T.N.T. comes from damage to the liver cells. This damage becomes apparent when Jaundice sets in; first noticed usually in the whites of the eyes and then by a yellow colour all over the body. Seven cases of this toxic jaundice are described by Dr Evans in an article in the Lancet, November 8, 1941, two of whom died. These dangers from T.N.T. are real, though they should not be exaggerated. It is necessary to understand why it may be dangerous and how the dangers can be avoided. It is of value to study the methods adopted in the Scottish factory mentioned above to keep the workers healthy. They can be classified under five heads: 1. Cleanliness. 2. Education of all personnel. 3. Selection of workers. 4. Investigation of absenteeism. 5. Diet. Cleanliness Perfect cleanliness of the workshops was the first requirement and probably the hardest to attain. Damp dusting of benches and damp sweeping of floors, with the usual exhaust ventilation, were insisted upon. Instructions were given that any dust falling on bench or floor must be instantly removed with a damp cloth, several times an hour if necessary. Eventually, a state of cleanliness was arrived at where "no spilt T.N.T. could be seen on floors or benches and no trace of fume or powder could be smelt or tasted in the air." It would be interesting to know at how many filling factories to-day this claim could be made. Personal cleanliness was also made possible by adequate lavatory accommodation, with a liberal number of basins supplying hot and cold water. "Every worker received a clean towel each morning for her own personal use, nail brushes, veils, special gloves and boots were also provided." Each worker also had a gargling mug, which they had to use before lunch and before going off in the evening, under supervision. A knitted respirator worked on the cross to give the necessary elastic grip of the nose, was also provided and its wear made compulsory. After each day's use, the respirator was cleansed and sterilized by washing in boiling water and then ironing. 29 21/2049